The nutritional content of supermarket beverages: a cross-sectional analysis of New Zealand, Australia, Canada and the UK. Issue 13 (7th February 2018) - Chepulis, Lynne; Mearns, Gael; Hill, Shaunie; Wu, Jason HY; Crino, Michelle; Alderton, Sarah; Jenner, Katharine
Abstract: Objective: To compare the nutritional content, serving size and taxation potential of supermarket beverages from four different Western countries. Design: Cross-sectional analysis. Multivariate regression analysis and χ 2 comparisons were used to detect differences between countries. Setting: Supermarkets in New Zealand (NZ), Australia, Canada and the UK. Subjects: Supermarket beverages in the following categories: fruit juices, fruit-based drinks, carbonated soda, waters and sports/energy drinks. Results: A total of 4157 products were analysed, including 749 from NZ, 1738 from Australia, 740 from Canada and 930 from the UK. NZ had the highest percentage of beverages with sugar added to them (52 %), while the UK had the lowest (9 %, P <0·001). Differences in energy, carbohydrate and sugar content were observed between countries and within categories, with UK products generally having the lowest energy and sugar content. Up to half of all products across categories/countries exceeded the US Food and Drug Administration's reference single serving sizes, with fruit juices contributing the greatest number. Between 47 and 83 % of beverages in the different countries were eligible for sugar taxation, the UK having the lowest proportion of products in both the low tax (5–8 % sugar) and high tax (>8 % sugar) categories. Conclusions: There is substantial difference between countries in the mean energy, serving size and proportion of products eligible for fiscal sugar taxation. Current self-regulatory approaches used in these countries may not be effective to reduce the availability, marketing and consumption of sugar-sweetened beverages and subsequent intake of free sugars.